Mid-term safety and efficacy in small intracranial aneurysm coiling: results from TARGET® nano prospective independent core lab adjudicated multicenter registry - Ashouri, Yazan; Paul, Alexandra R.; Puri, Ajit; Liaw, Nicholas; Majjhoo, Aniel; Taqi, Asif; Rai, Ansaar; Badruddin, Aamir; Alshekhlee, Amer; Naravetla, Bharath; Rayes, Mahmoud; Lawson, Matthew; et al. (Frontiers in Neurology, 2024)
Background: The primary objective is to evaluate the safety and effectiveness of Stryker 2nd generation Target® Nano Coils in the treatment of ruptured and unruptured small (<7mm) intracranial aneurysms.Methods: The TARGET Registry is a prospective, two-arm study with independent medical event monitoring and core-lab adjudication. This paper describes the second arm of the TARGET registry. Patients with de novo intracranial aneurysms were embolized with 2nd generation TARGET Nano coils in 12 US centers. The primary efficacy outcome was adequate aneurysm occlusion (RR occlusion grade I-II) on follow-up. Primary safety outcome was treatment-related morbidity and mortality. Secondary outcomes included aneurysm packing density immediately post-procedure, immediate adequate occlusion, aneurysm re-access rate, retreatment rate and clinical outcomes using modified rankin scale. . A secondary analysis investigated the influence of using Nano-predominant coils (≥2/3 of total coil-length) vs non-Nano-predominant coils (<2/3 of total length).Results: 150 patients with 155 aneurysms met the inclusion and exclusion criteria. (31%) patients with ruptured and (69%) with unruptured aneurysms were treated using TARGET coils. Median age was 58.8 (SD 12.7), 74.7% were females, and 80% were Caucasians. Mean follow-up was 5.23 (SD 2.27) months. Peri-procedural mortality was seen in 2.0% of patients. Good outcome at discharge (mRS 0-2) was seen in 81.3% of the cohort. The median packing density (SD) was 29.4% (14.9). Mid-term complete/near complete occlusion rate was seen in 96% of aneurysms and complete obliteration was seen in 75.2% of aneurysms. Patients treated predominantly with Nano coils had higher PD (32.6% vs 26.1%, P<.001). There was no significant difference in clinical and angiographic outcomes. The mid-term mRS0-2 was achieved in 106/109 (97.2%) patients. Allcause mortality was 5/115 (4.3%).In the multicenter TARGET Registry, 75.8% of aneurysms achieved mid-term complete occlusion, and 96% achieved complete/near complete occlusion with excellent independent functional outcome.